Analyzing the Safeguarding Our Communities Act: Patch for Patch Return Policy in Ontario - Soo-Min Kim (McMaster University Library Press, 2018)
Fentanyl is prescribed to patients suffering from severe chronic pain. Transdermal patches are the best mode of delivery for patients who have developed tolerance for opioids. However, used patches still contain fentanyl that can be extracted and misused, with potentially severe consequences. To address this issue, patients who are prescribed fentanyl patches in Ontario are now required to return previously dispensed patches to receive new patches under the Safeguarding Our Communities Act: Patch for Patch (P4P) Return Policy. The problem is significant in Ontario because the province has the largest annual dispense rate of high-dose prescription fentanyl (112 units per 1,000 population) in Canada even though the prevalence rate of chronic pain is lower than the national reported range (16.6% in Ontario versus 19.6 to 21.9% in other provinces, according to Gomes et al. 2014). The primary goal of this reform is to instill responsible use of fentanyl patches, and to improve safety for patients and the public by having a central disposal process. The reform was modeled after a community initiative that was pioneered in North Bay after receiving great support from health professional colleges and communities that voluntarily integrated the program prior to the introduction of Bill 33. Preliminary data suggest that the P4P policy is positively received by health professionals, although ongoing evaluation is needed to assess the effectiveness of the policy in reducing misuse and abuse of prescribed fentanyl patches.